2020
DOI: 10.1371/journal.pone.0239917
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of global health competencies: A scoping review on target audiences, levels, and pedagogy and assessment strategies

Abstract: Background As the field of global health expands, the recognition of structured training for field-based public health professionals has grown. Substantial effort has gone towards defining competency domains for public health professionals working globally. However, there is limited literature on how to implement competency-based training into learning curricula and evaluation strategies. Objectives This scoping review seeks to collate the current status, degree of consensus, and best practices, as well as gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 54 publications
(130 reference statements)
0
20
0
2
Order By: Relevance
“…Despite these previous reviews providing excellent discussions on the educational strategy landscape, there have been limited publications specifically focused on assessment. The most relevant is a recent scoping review by Schleiff et al [ 126 ], which examined literature on competency-based training incorporation into curricula and evaluation strategies, with a subset focused on clinical and allied health professional training. This review identified three major forms of evaluation tools, including self-assessment surveys, assessment from multiple stakeholders’ perspectives, and mixed-methods approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these previous reviews providing excellent discussions on the educational strategy landscape, there have been limited publications specifically focused on assessment. The most relevant is a recent scoping review by Schleiff et al [ 126 ], which examined literature on competency-based training incorporation into curricula and evaluation strategies, with a subset focused on clinical and allied health professional training. This review identified three major forms of evaluation tools, including self-assessment surveys, assessment from multiple stakeholders’ perspectives, and mixed-methods approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Timmerberg et al (17) reported that standardized clinical practicing contributed to enhancement of responsibility, self-awareness, and timeliness, which are essential for development of professionalism. Assessment of PTs competency by using standards of EPTCQ is supported by Schleiff et al (18) who emphasized the importance of credibility and accountability of the profession by providing professionals, students, educators and assessors with defined standards of practice and underpin professional occupation descriptions, specific work tasks, and performance criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The LMIC-based fellows tended to have a more technical focus on program implementation while those in US-based positions focus more on advising and guiding colleagues by identifying, developing, and packaging global knowledge and supporting programs to utilize it. This has been seen in other programs as well that focus on diverse target audiences [9,14,15,[19][20][21][22][23]. The LOs of LMIC-based fellows are largely aimed at developing and then directly applying skills-such as data analysis, language, and communications-in their work.…”
Section: Plos Onementioning
confidence: 99%
“…Global health training opportunities have expanded dramatically in the past few decades [8][9][10][11][12]. Pedagogical approaches to supporting emerging leaders in this field have begun to take shape, but more experience and further evidence and documentation of strategies and outcomes of these programs are needed [7,10,[13][14][15][16]. In recent years there has been an increasing focus on building the global health workforce, with the delivery of technical and leadership focused training programs [12,17,18].…”
Section: Introductionmentioning
confidence: 99%